Pengaruh Konsentrasi Larutan Asam Asetat Dan Lama Perendaman Terhadap Karakteristik Gelatin Kulit Ikan Mahi-Mahi (Coryphaena hippurus) - Fauziyyah, Puti; Yusasrini, Ni Luh Ari; Darmayanti, Luh Putu Trisna (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 2 No 2 (2017), 2018)
The aim of this research was to know the effect of acetic acid concentration and soaking time on characteristics of mahi-mahi ( Coryphaena hippurus ) fish skin gelatin and to know the right acetic acid concentration and soaking time to produce the best characteristics of gelatin. The design used in this research was completely randomized factorial design with the factors was concentration of acetic acid in three levels i.e  0,5%, 1%, 1,5% and soaking time in three levels i.e 12, 18 and 24 hours. Data were analyzed by analysis of variance, followed by Duncan Multiple Range Test (DMRT). The result of this research showed that the interaction between acetic acid concentration and soaking time had a very significant effect on yield, pH, gel strength, viscosity, lightness, moisture content, protein content and significant effect on ash content. The best characteristic of mahi-mahi fish skin gelatin at concentration of acetic acid 0,5% for 12 hours with yield of 26,38%, pH value 5,13, gel strength 107,12 bloom, viscosity 16,40 cP, lightness 29,77, water content 8,47%, ash content of 1,11%, and protein content of 90,4%.